2017
DOI: 10.1111/cdev.12840
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Peer Predictors of Change in Attachment Security From Adolescence to Adulthood

Abstract: Interview, self-report, peer-report, and observational data were used to examine parent and peer relationship qualities as predictors of relative changes in attachment security in a community sample of adolescents followed from age 14 to 24. Early maternal supportive behavior predicted relative increases in attachment security from adolescence to adulthood, whereas psychological control and interparental hostile conflict predicted relative decreases. Peer predictors of relative increases in security included c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 49 publications
1
38
0
1
Order By: Relevance
“…Psychological control, defined as the control that parents put in place to intrude into the psychological world of the child, undermines children's adequate psychological functioning (Soenens & Vansteenkiste, ). As expected, the construct is negatively correlated with peer support and self‐esteem, and positively related to anxiety and aggressive behaviour in children (Allen, Grande, Tan, & Loeb, ; Costa, Soenens, Gugliandolo, Cuzzocrea, & Larcan, ; Murray, Dwyer, Rubin, Knighton‐Wisor, & Booth‐LaForce, ; Wuyts, Vansteenkiste, Soenens, & Assor, ). A recent meta‐analysis (Endendijk, Groeneveld, Bakermans‐Kranenburg, & Mesman, ) has shown that although the effect of paternal and maternal psychological control is very similar for both boys and girl, parents tend to be more psychologically controlling with boys than with girls.…”
Section: Introductionmentioning
confidence: 54%
“…Psychological control, defined as the control that parents put in place to intrude into the psychological world of the child, undermines children's adequate psychological functioning (Soenens & Vansteenkiste, ). As expected, the construct is negatively correlated with peer support and self‐esteem, and positively related to anxiety and aggressive behaviour in children (Allen, Grande, Tan, & Loeb, ; Costa, Soenens, Gugliandolo, Cuzzocrea, & Larcan, ; Murray, Dwyer, Rubin, Knighton‐Wisor, & Booth‐LaForce, ; Wuyts, Vansteenkiste, Soenens, & Assor, ). A recent meta‐analysis (Endendijk, Groeneveld, Bakermans‐Kranenburg, & Mesman, ) has shown that although the effect of paternal and maternal psychological control is very similar for both boys and girl, parents tend to be more psychologically controlling with boys than with girls.…”
Section: Introductionmentioning
confidence: 54%
“…Research has shown that the quality of adolescents’ social relationships plays a significant role in their well-being [18,29]. Although in adolescence the relationship with the peer group acquires greater relevance than in childhood, parent-child relationships continue to be a primary source of well-being for the adolescent [25]. One of the variables which influences the development of emotional competencies is parental attachment, in fact, adolescents who maintain a secure attachment to their parents are more capable to perceive, name, express and regulate their emotions [77].…”
Section: Discussionmentioning
confidence: 99%
“…Children whose primary caregivers, usually the mother and the father, were sensitive and responded appropriately to their needs, establish a bond of secure parental attachment and, as a consequence, foster a basic attitude of trust towards others [24]. From adolescence to mid-life, this could translate into more fluid and positive interpersonal relationships, thanks to more effective emotional and interpersonal skills [23,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who developed a secure attachment to their parents are more likely to establish a secure attachment bond with their peers [22]. The study of peer attachment is of great interest especially in adolescence, when social relationships become more complex [23,24]. A secure peer attachment is defined as a relationship established on a basis of trust, along with the belief that the other person will respect one' own needs and desires, and she will be able to both understand and respond if when communicating our feelings [25].…”
Section: Importance Of Secure Peer Attachment Relationshipsmentioning
confidence: 99%